PENINGKATAN KEMAMPUAN IBU MELAKUKAN STIMULASI PERKEMBANGAN MAKAN TODDLER PICKY EATER - Santi, Eka (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2016)
Stimulation of the development of eating is an activity that enhances the ability of children tobehavior when eating. The practice of feeding is strongly influenced by the mother's role,particularly in children toddler who develop their independence, one of which is eaten. Motherability stimulating the benchmark eating behavior in children. Quasy experiment with sample 21respondents mothers who have toddler with difficult feeding in Puskesmas North Banjarbaruthrough purposive sampling technique and Wilcoxon Sign Rank Test is used in this study. Theresult showed increase the mother's ability stimulating the development of eating between firstand second observation with p value = 0.025 into p value = 0.014. However, at the componentsof health belief model does not give effect to the mother's ability. Perceived vulnerability p =0.317; perceived seriousness p = 0.564, perceived barrier p = 0.157 and perceived benefit p =1.000. Early detection oral motor development should include the part ofchild development.